Influence of extrinsic factors on guanidine hydrochloride denaturation of Bacillus licheniformis α-amylase / Salanee Kandandapani - Salanee , Kandandapani (2016)
The influence of buffer composition on the conformational stability of native and calcium-depleted Bacillus licheniformis α-amylase (BLA) was investigated against guanidine hydrochloride (GdnHCl) denaturation using circular dichroism, fluorescence and UV-difference spectroscopy. Buffers used in these experiments were: 0.05 M sodium phosphate buffer, pH 7.5, 0.15 M Tris-HCl buffer, pH 7.5, 0.15 M HEPES buffer, pH 7.5 and 0.15 M MOPS buffer, pH 7.5. Differential effects of buffer composition on GdnHCl denaturation of BLA were evident from the magnitude of these spectral signals, which followed the order: sodium phosphate > Tris-HCl > HEPES > MOPS. These effects became more pronounced when calcium-depleted BLA was used in the incubation mixture as revealed by a lower relative mean residue ellipticity, lower relative fluorescence intensity, and higher change in emission maximum. Depletion of calcium from BLA suggested a decrease in the protein conformational stability. Gel chromatographic analyses of native, 3 M GdnHCldenatured and 6 M GdnHCl-denatured BLAs were made in different runs on Sephacryl S-200 HR column (1.0×30 cm), equilibrated with these buffers. The results obtained clearly suggested formation of similar denatured states and aggregated forms of BLA in 3 M and 6 M GdnHCl in the presence of these buffers. However, quantitative differences in BLA aggregation were noticed in these buffers in the presence of 6 M GdnHCl. In view of the above, spectral results on BLA stability against GdnHCl obtained with different probes (MRE, fluorescence intensity and emission maximum) in different buffers should be treated with caution.